IMPLEMENTASI TEORI BELAJAR BEHAVIORISTIK MELALUI STRATEGI PEMBELAJARAN EKSPOSITORI PADA MATA PEMBELAJARAN QUR’AN HADIST MATERI IMAN KEPADA ALLAH DI KELAS 1 MI ISLAMIYAH 2 PENGANTEN DALAM KURIKULUM MERDEKA - Firda Zakiyatur Rofi'ah; Dwi Nur Alfi Lutfiyatin; Alfiana Putri Ramadhani; Rika Apriliandari; Nazila Aulia Rosyida; Hilha Susyana Meilia; Nur Laily Maratum Mubarokah; Sila Wardatus Solikhah; Siti Alimatus Sa Adah; Nurul Hidayah; Moh. Imron Rosadi; Lailatul Fitriah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study explores the implementation of behaviorist learning theory through expository teaching strategies in the Qur'an Hadist subject, focusing on the topic of faith in Allah (Iman kepada Allah) for first-grade students at MI Islamiyah 2 Penganten under the Independent Curriculum (Kurikulum Merdeka). Using a qualitative descriptive method and case study approach, data were collected through observation, interviews, and document analysis. The results indicate that the teacher utilized an expository strategy by providing structured explanations, direct stimulus, and consistent reinforcement techniques. Positive reinforcement such as praise and rewards played a crucial role in maintaining student focus and improving memorization of verses and key concepts. Students demonstrated increased attentiveness, improved recall, and active engagement during learning sessions. These findings affirm that behaviorist-based approaches remain relevant and effective, especially in early primary education and in delivering abstract religious concepts, when adapted within the framework of the Merdeka Curriculum